Another tool for the fork‐in‐the‐road toolbox. Issue 7 (7th June 2019) - Butman, Samuel M.
Key Points: A provisional stent strategy for bifurcation disease is a good rule of thumb. The Tryton bifurcation stent is an additional potential useful tool for use in complex coronary disease. If and when this device has a drug‐eluting side branch, its true role may be clearer.